Preferensi Konsumen Dan Dampaknya Pada Minat Beli - Bob Foster (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2018)
Nowadays, the communication equipment companies face the fierce competition. The company tries to be the market leader. Based on data obtained in the last five years, Samsung is the smartphone market leader that topped the ranks in any types of communication equipment. Now, technology is a tool that enables people to connect with one another easily. The population in this study is all consumers of Samsung products in Bandung. The variables as brand image, brand trust, and product quality are used to explain the consumer preferences. The 100 people were used as samples based on the Green model. This study tries to find the impact of customer preferences that influence the buying interest. This study uses primary data by distributing the questionnaires to the consumers of Samsung products in Bandung. The sampling technique used in this study is the non-probability sampling with purposive sampling technique. The research uses the quantitative method, and the analytical tool is the multiple regression analysis. SPSS is the software that supports this research. The results show that all research variables both simultaneously and partially affect buying interest.